Lack of effect of cold water prawns on plasma cholesterol and lipoproteins in normo-lipidaemic men - Isherwood, C.; Wong, M.; Jones, W. S.; Davies, I. G.; Griffin, B. A. (Cellular and Molecular Biology, 2010)
Objective: Dietary guidelines for the prevention of coronary heart disease (CHD) have restricted the intake of foods rich in dietary cholesterol, on the grounds that the dietary cholesterol will increase blood cholesterol. In the case of shellfish, this recommendation may limit the intake of a valuable dietary source of long chain n-3 polyunsaturated fatty acids (LC n-3 PUFA). The objective of this study was to undertake a dietary intervention to determine the effects of cold water prawns on plasma lipids and lipoproteins. Methods: 23 healthy male subjects were randomised to receive either 225 g of cold water prawns or an equivalent weight of fish (‘crab') sticks as a control for 12 weeks in a cross-over design. Blood samples were taken at the beginning and end of each intervention for the determination of plasma lipids and lipoproteins by routine enzymatic assays and iodixanol density gradient centrifugation respectively. Results: The diets were well matched for the intake of total energy and macronutrients, and body weight remained stable throughout the study. The prawn intervention increased the intake of dietary cholesterol to 750 mg/d against 200mg/d on the control. The intake of LC n-3 PUFA from prawns was estimated to be between 0.5-0.7g/d. The consumption of prawns produced no significant effects on the concentration of plasma total or LDL cholesterol, triacylglycerol, HDL cholesterol or apolipoproteins A-I and B relative to the control, or within each intervention group over time. There was also no significant effect on LDL density (particle size) relative to the control, or any difference between and within treatments in total plasma lipoprotein profiles by density gradient centrifugation. Conclusion: These findings provide evidence to suggest that the consumption of cold water prawns, at least in healthy, male subjects, should not be restricted on the grounds of this seafood producing an adverse effect on plasma LDL cholesterol.